Estimating concentration of toxic ions Arsenic in water by using Photonic Crystal Fiber based on Surface Plasmon Resonance (SPR) (Baghdad Science Journal, 2024)
In this work, an enhanced Photonic Crystal Fiber (PCF) based on Surface Plasmon Resonance (SPR) sensor using a sided polished structure for the detection of toxic ions Arsenic in water was designed and implemented. The SPR curve can be obtained by polishing the side of the PCF after coating the Au film on the side of the polished area, the SPR curve can be obtained. The proposed sensor has a clear SPR effect, according to the findings of the experiments. The estimated signal to Noise Ratio (SNR), sensitivity (S), resolution (R), and Figures of merit (FOM) are approaching; the SNR is 0.0125, S is 11.11 μm/RIU, the resolution is 1.8x〖10〗^(-4), and the FOM is 13.88 for Single-mode Fiber- Photonic Crystal Fiber- single mode Fiber (SMF-PCF-SMF). While the effective performance parameters for Multi-Mode Fiber- Photonic Crystal Fiber- Multi-Mode Fiber (MMF-PCF-MMF) such as the sensitivity is approaching 9.5 μm/RIU, SNR is 0.0173, FOM is10.86 and the resolution is 4x〖10〗^(-4) is achieved. The concentrations were calculated practically and theoretically for each of the sensors, and it was found that the practical concentrations that were obtained are close or equal to the concentrations that were theoretically obtained through the dilution law, where the concentrations were obtained 0.096, 0.15, 0.26, 0.38, 0.49 practically and 0.1, 0.2 and 0 3, 0.4 and 0.5 theoretically For SMF-PCF-SMS, concentrations of 0.089, 0.16, 0.23, 0.34, and 0.45 were practically obtained, and 0.1, 0.2, 0.3, 0.4, and 0.5 theoretically for MMF-PCF-MMF. The suggested sensor has a strong mechanical structure, low cost, and easy fabrication, allowing it to provide a greater measurement range and action area to the measured samples without lengthening the sensor.